Unique and Conserved Features of the Barley Root Meristem - Kirschner, Gwendolyn K.; Stahl, Yvonne; Von Korff, Maria; Simon, Rüdiger (Frontiers in Plant Science, 2017)
Plant root growth is enabled by root meristems that harbour the stem cell niches as a source of progenitors for the different root tissues. Understanding the root development of diverse plant species is important to be able to control root growth in order to gain better performances of crop plants. In this study, we analysed the root meristem of the fourth most abundant crop plant, barley (Hordeum vulgare). Cell division studies revealed that the barley stem cell niche comprises a Quiescent Center (QC) of around 30 cells with low mitotic activity. The surrounding stem cells contribute to root growth through the production of new cells that are displaced from the meristem, elongate and differentiate into specialized root tissues. The distal stem cells produce the root cap and lateral root cap cells, while cells lateral to the QC generate the epidermis, as it is typical for monocots. Endodermis and inner cortex are derived from one common initial lateral to the QC, while the outer cortex cell layers are derived from a distinct stem cell. In rice and Arabidopsis, meristem homeostasis is achieved through feedback signalling from differentiated cells involving peptides of the CLE family. Application of synthetic CLE40 orthologous peptide from barley promotes meristem cell differentiation, similar to rice and Arabidopsis. However, in contrast to Arabidopsis, the columella stem cells do not respond to the CLE40 peptide, indicating that distinct mechanisms control columella cell fate in monocot and dicot plants.